Primary and secondary dysmenorrhea: symptoms, risk factors, diagnosis, and treatment – review - Krzemińska, Paulina; Kołodziej, Joanna; Biniewicz, Arkadiusz (Quality in Sport, 2024)
Dysmenorrhea, or painful uterine contractions during menstruation in women, is a common condition. It may affect up to 90% of patients in a doctor’s office. Depending on the severity of symptoms, it may cause discomfort or prevent normal functioning in everyday life. Some women do not realize that this is not a normal symptom during menstruation. Unfortunately, lack of exercise, smoking, or drinking alcohol only increases the symptoms. A medical history and physical examination of the patient are important steps in finding the cause. Primary dysmenorrhea is primarily associated with the pathogenesis of prostaglandins and leukotrienes, which generate inflammation and pain. However, it has nothing to do with pelvic pathology. It usually first appears in young women during puberty, up to 24 months after their first period. If the history and physical examination are not clear about the primary cause of pain, a secondary cause should be considered. For this purpose, a transvaginal ultrasound examination should be performed. The most common secondary pathology is endometriosis. In the treatment of primary and secondary diseases, physical exercises and warm compresses are beneficial, which women are often unaware of. First-line pharmacological treatment may include NSAIDs or combined oral estrogen-progestogen hormonal therapy. The purpose of this review is to provide knowledge about the symptoms, risk factors, diagnosis, and treatment of dysmenorrhea.